Epigenetic biomarkers indicate islet cell death in xenotransplantation. (26th January 2020) - Faulk, Christopher; Mueller, Kate R.; Cheishvili, David; Colwell, Mathia; Pepin, Anne‐Sophie; Syzf, Moshe; Hering, Bernhard J.; Burlak, Christopher
Abstract: Background: Xenotransplantation of porcine islets has emerged in recent decades as a potential treatment for type 1 diabetes (T1D). Current methods of detection, indicative of successful engraftment, occur downstream of actual islet death. Epigenetic biomarkers can be detected in circulating cell‐free DNA (cfDNA) to provide an earlier indication of graft dysfunction. Aims: The present study identified a biomarker of islet death using differential methylation of the insulin gene, INS, originating from β‐cells in porcine islets. Materials & Methods: Pyrosequencing primers specific for porcine INS were designed to quantify hypomethylation along 12 cysteine‐guanine dinucleotide (CpG) sites, including three sites in the cyclic adenosine monophosphate (cAMP) response element (CRE) binding protein 2 (CRE2) binding region of the 5′ untranslated region (UTR) and nine sites within intron 2. Results: PCR amplification of bisulfite‐converted DNA combined with pyrosequencing data support the conclusion that hypomethylated porcine INS is specific to islet origin. Conclusion: Moreover, the results of this study indicate a highly specific epigenetic biomarker, capable of detecting a single islet, supporting the measurement of cfDNA as a biomarker for transplanted islet death. Defining the epigenetic characteristics of porcine‐derived islets within cfDNA will be crucial to develop a better understanding of graft survival immunology for transplantation.